CT-FFR by expanding coronary tree with Newton–Krylov–Schwarz method to solve the governing equations of CFD - Guo, Weifeng; He, Wei; Lu, Yige; Yin, Jiasheng; Shen, Li; Yang, Shan; Jin, Hang; Wang, Xinhong; Jun, Jiang; Hu, Xinyang; Liang, Jianwen; Wei, Wenbin; et al. (European heart journal. Imaging methods and practice, 2024)
Abstract Aims A new model of computational fluid dynamics (CFD)-based algorithm for coronary CT angiography (CCTA)-derived fractional flow reserve (FFR) (CT-FFR) analysis by expanding the coronary tree to smaller-diameter lumen (0.8 mm) using Newton–Krylov–Schwarz (NKS) method to solve the three-dimensional time-dependent incompressible Navier–Stokes equations has been developed; however, the diagnostic performance of this new method has not been sufficiently investigated. The aim of this study was to determine the diagnostic performance of a novel CT-FFR technique by expanding the coronary tree in the CFD domain. Methods and results Six centres enrolled 338 symptomatic patients with suspected or known coronary artery disease (CAD) who prospectively underwent CCTA and FFR. Stenosis assessment in CCTA and CT-FFR analysis were performed in independent core laboratories. Haemodynamically significant stenosis was defined by a CT-FFR and FFR ≤ 0.80, and anatomically obstructive CAD was defined as a CCTA with stenosis ≥ 50%. Diagnostic performance of CT-FFR was evaluated against invasive FFR using receiver operating characteristic (ROC) curve analysis. The correlation between CT-FFR and invasive FFR was analysed using the Spearman correlation coefficient and Bland–Altman analysis. Intra-observer and inter-observer agreements were evaluated utilizing the intraclass correlation coefficient (ICC). In this study, 338 patients with 422 targeted vessels were investigated, revealing haemodynamically significant stenosis in 31.1% (105/338) of patients and anatomically obstructive stenosis in 54.1% of patients. On a per-vessel basis, the area under the ROC curve for CT-FFR was 0.94 vs. 0.76 for CCTA (P < 0.001). Per-vessel accuracy, sensitivity, specificity, positive predictive value, and negative predictive value were 89.8%, 89.3%, 90.0%, 79.0%, and 99.2%, respectively, for CT-FFR and were 68.4%, 82.8%, 62.3%, 48.1%, and 89.6%, respectively, for CCTA stenosis. CT-FFR and FFR were well correlated (r = 0.775, P < 0.001) with a Bland–Altman bias of 0.0011, and limits of agreement from −0.1509 to 0.1531 (P = 0.770). The ICCs with CT-FFR for intro- and inter-observer agreements were 0.919 (95% CI: 0.866–0.952) and 0.909 (95% CI: 0.851–0.945), respectively. The average computation time for CT-FFR analysis was maintained at 11.7 min. Conclusion This novel CT-FFR model with the inclusion of smaller lumen provides high diagnostic accuracy in detecting haemodynamically significant CAD. Furthermore, the integration of the NKS method ensures that the computation time remains within an acceptable range for potential clinical applications in the future. Graphical Abstract Graphical Abstract Diagnostic performance of CCTA and CT-FFR to identify haemodynamically significant coronary artery disease. The receiver operating characteristic curve and corresponding area under the curve describing the diagnostic performance of CCTA and CT-FFR to identify haemodynamically significant coronary artery disease as defined by invasive coronary angiography with fractional flow reserve at (A) the patient level and (B) the vessel level.